Association of self-efficacy and mental toughness with sport performance in Brazilian futsal athletes - Aizava, Paulo Vitor Suto; Codonhato, Renan; Fiorese, Lenamar (Frontiers in Psychology, 2023)
Introduction: self-efficacy is considered a component of mental toughness, but there are few studies investigating the relationship of sport self-efficacy with mental toughness in performance athletes, especially in team sports. Objective: The objective was to examine the impact of sport self-efficacy mediated by mental toughness on the sport performance of Brazilian futsal athletes. Methods: The sample was composed of five adult male teams participating in the National Futsal League 2020, totaling 77 athletes. As instruments, we used: athlete identification sheet, Perceived Sport Self-Efficacy Scale (PSE), Mental Toughness Index (MTI) questionnaire and the performance data from the National Futsal League 2020 (NFL). The data were analyzed using the Kolmogorov-Smirnov test, Mann-Whitney "U" test, Spearman's correlation, network analysis (LASSO), with the indicators of centrality: strength, proximity and degree of Intermediation (p<0.05). Results: The results showed that the investigated sample presented high levels of Perceived Sport Self-Efficacy (PSE) (Md=4,66) and mental toughness (MT) (Md=6,44). PSE presented a positive relationship with the number of wins, and negative relationships with the number of red cards and wrong passes (r=-0,08). MT indirectly influenced these variables through its connection with PSE (r=0,30). The best ranked teams presented higher amounts of goals for, fouls, shots on goal, tackles, assists and wins. The time of practice revealed an inverse relationship with the number of defeats, while age was positively related to the number of wrong passes (r=0,09). The centrality indicators showed that the number of games stood out as theRunning Title 2 most central variable in the network, due to its degree of strength, proximity and intermediation. Moreover, the high degree of proximity and intermediation of the tackles made presented a connection with the number of assists (γ=0.25; n=77). Conclusion: We can conclude that sport self-efficacy and mental toughness are intervening factors in the sport performance of Brazilian futsal athletes.